IMMUNOMODULATORY EFFECT OF CURCUMA LONGA IN MICE - Abeer L. Mohammed (Basrah Journal of Veterinary Research)
This study was designed to find out the effect of oral inoculation of aqueous extract of Curcuma Longa at two doses (1 and 5) mg/ kg body weight daily for 4 weeks on the immune response of Balb/c mice by estimating of serum concentration of interleukin-2 (IL-2) , interleukin-4 (IL-4), interleukin-10 (IL-10) and interferon gamma (INF-γ) using ELISA test. The present results revealed that significant increase (p